INCARCERATED LITTRE'S FEMORAL HERNIA: CASE REPORT AND REVIEW OF THE LITERATURE - Mirza, Muhammad S. (Journal of Ayub Medical College Abbottabad, 2007)
Meckel's diverticulum is the most prevalent congenital abnormality of the gastrointestinal tract associated with many diverse and unusual complications. Meckel's Diverticulum is a true diverticulum comprising all intestinal layers. Its diagnosis is usually difficult despite the availability of modern tools.A high index of suspicion is mandatory. In most cases it is an incidental finding. Hernial strangulation of Meckel's diverticulum (Littre's Hernia) is a rare anatomo-clinical form. Surgery is the mainstay of treatment. Keyword: Litter's Hernia